2017
DOI: 10.1039/c7ta07566a
|View full text |Cite
|
Sign up to set email alerts
|

Salt-templated synthesis of defect-rich MoN nanosheets for boosted hydrogen evolution reaction

Abstract: The ultra-stable highly efficient HER over a wide pH range on defect-rich MoN nanosheets synthesized using a modified salt-template process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 50 publications
2
74
0
Order By: Relevance
“…[ 9 ] Up to now, diverse 2D materials have been reported in addition to graphene: materials with layered structures such as transition metal dichalcogenides (TMDs, such as MoS 2 , WS 2 , MoSe 2 , and WSe 2 ), [ 10–13 ] transition metal oxides (TMOs, like δ‐MnO 2 , MoO 3 , and LaNb 2 O 7 ), [ 14–16 ] layered double hydroxides (LDHs, e.g., Mg 6 Al 2 (OH) 16 CO 3 ∙4H 2 O), [ 17 ] hexagonal‐boron nitride ( h ‐BN), [ 2,18 ] transition metal halides (such as MoCl 2 and CrCl 3 ), [ 19 ] black phosphorus, [ 20 ] graphitic carbon nitride ( g ‐C 3 N 4 ), [ 5 ] MXene (such as Ti 2 C and Ti 3 CN), [ 21–25 ] and clays (for instance, [(Mg 3 )(Si 2 O 5 ) 2 (OH) 2 ] and [(Al 2 )(Si 3 Al)O 10 (OH) 2 ]K). [ 19 ] Notably, many nonlayered structure species can also form 2D morphology with specific synthetic methods, largely expanding the 2D family (such as hexagonal‐MoO 3 ( h ‐MoO 3 ), hexagonal‐WO 3 ( h ‐WO 3 ), [ 15 ] transition metal nitrides (TMNs), [ 26,27 ] and transition metal phosphides (TMPs)). [28] To exploit the applications of 2D materials, the development of a synthetic method should be prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Up to now, diverse 2D materials have been reported in addition to graphene: materials with layered structures such as transition metal dichalcogenides (TMDs, such as MoS 2 , WS 2 , MoSe 2 , and WSe 2 ), [ 10–13 ] transition metal oxides (TMOs, like δ‐MnO 2 , MoO 3 , and LaNb 2 O 7 ), [ 14–16 ] layered double hydroxides (LDHs, e.g., Mg 6 Al 2 (OH) 16 CO 3 ∙4H 2 O), [ 17 ] hexagonal‐boron nitride ( h ‐BN), [ 2,18 ] transition metal halides (such as MoCl 2 and CrCl 3 ), [ 19 ] black phosphorus, [ 20 ] graphitic carbon nitride ( g ‐C 3 N 4 ), [ 5 ] MXene (such as Ti 2 C and Ti 3 CN), [ 21–25 ] and clays (for instance, [(Mg 3 )(Si 2 O 5 ) 2 (OH) 2 ] and [(Al 2 )(Si 3 Al)O 10 (OH) 2 ]K). [ 19 ] Notably, many nonlayered structure species can also form 2D morphology with specific synthetic methods, largely expanding the 2D family (such as hexagonal‐MoO 3 ( h ‐MoO 3 ), hexagonal‐WO 3 ( h ‐WO 3 ), [ 15 ] transition metal nitrides (TMNs), [ 26,27 ] and transition metal phosphides (TMPs)). [28] To exploit the applications of 2D materials, the development of a synthetic method should be prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Figure F shows the high‐resolution HRTEM, FFT images and the corresponding arrangement of Mo and N atoms. The HRTEM and FFT images exhibited the high crystallinity of the prepared MoN nanosheets, and the interplanar spacing of (200) the facets was 2.48 Å, which is in the reported range of 2.44 to 2.50 Å . The arrangement of Mo and N atoms shows that the family of crystal planes of the lateral directions of the prepared MoN sheets should be (100).…”
Section: Resultsmentioning
confidence: 87%
“…3,8,15,18 Xiao et al reported a promising template-assisted method to synthesize 2D h-MoO3@NaCl. 19 Then, 2D MoN was successfully synthesized by ammoniating the 2D h-MoO 3 @NaCl, 3,8,9,12 which exhibited very high volumetric capacitance and excellent rate performance 3 , and efficiently photo-/electro-catalyzed | 7179 SUN et al the hydrogen evolution reaction. 8,9,12 Joshi et al 18 synthesized 2D MoN nanosheets by ammoniating 2D nanosheets of MoO 3 prepared via a hot-filament chemical vapor deposition (HFCVD) process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their high surface area/volume ratio with sufficient exposed active sites and rapid charge transport, 2 D nanosheets (NSs) show better catalytic performance than other structures . In addition, if the thickness of ultrathin NSs is less than 5 nm, the catalytic performance will show further improvement because of the under‐coordinated surface sites.…”
Section: Two‐dimensional Nanostructuresmentioning
confidence: 99%